ANALISIS PENGARUH KEPUASAN GAJI DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP TURNOVER INTENTION (Studi pada karyawan kantor pusat Bank Jateng) - Miftah, Muhammad; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
Turnover intention is a serious problem and can not be taken lightly within a company. In the current era of globalization, there are still many companies that experience turnover intention problems, which causes many employees in the company to decide to leave or move from the company where they work today. One of the companies that experienced this problem was Bank Jateng. This research aims to examine and analyze the effect of salary satisfaction and career development on job satisfaction and to know the impact of both variables on turnover intention at PT. Bank Jateng.Data collecting method used in this research is a questionnaire with a sample of 100 employees of the Central Bank headquarters. The technique of sampling in this research using non-probability sampling method with purposive sampling technique, by choosing the appropriate samples with the objects and problems to be developed in the research.This research uses multiple linear regression analysis method to analize the data obtained in the research.The results of this study indicate that the variable of salary satisfaction and career development have positive and significant impact on job satisfaction, both also give negative and significant influence to turnover intention of employees of Bank Central Java head office. Job satisfaction variable in this research, also give negative and significant influence to turnover intention of employees of Bank Central Java head office. These variables give effect of 28,8% to job satisfaction and 46,9% to turnover intention. The remaining 71,2% for job satisfaction variation and 53,1% for variation of turnover intention influenced by other variables outside this research. From the result of path analysis showed that job satisfaction does not mediate the effect of pay satisfaction on turnover intention with value of t table equal to 1,93, while for career development variable proven to be mediated by job satisfaction with t table equal to 5,41.